Cutaneous recurrence of long term pulmonary sarcoidosis - literature review and case report - Julia Bargieł; Justyna Cabaj; Izabela Chmielewska; Marta Adamczyk-Korbel; Anna Grzywa-Celińska (Kazimierz Wielki University, 2023)
Sarcoidosis is a systemic granulomatous disease, the exact etiology of which is unknown. This paper presents a case of a patient with a long course of pulmonary sarcoidosis with exacerbation of the disease in the form of skin lesions.                A 50-year-old female patient was admitted to the Department of Tuberculosis and Lung Diseases, Medical University of Lublin, because of cervical lymphadenopathy. Based on the histopathological examination, she was diagnosed with sarcoidosis. The patient reported constant fatigue, throat tightness and difficulty swallowing, as well as decreased exercise tolerance. Computed tomography studies revealed small nodular changes in both lungs and mediastinal lymphadenopathy. The patient was actively monitored. The results of spirometry tests improved spontaneously and remained at a satisfactory level for years. After 15 years of follow-up, the patient reported skin lesions that are constantly progressing. Examination of the cut from the skin lesion confirmed skin sarcoidosis. This case report highlights the varied course of sarcoidosis, which, as a multi-system disease, may show various manifestations. In clinical practice, therefore, one should consider the possibility of disease progression and transmission to multiple organs. It is important that the patient is under constant observation and that new lesions undergo differential diagnosis and histopathological examination.